Genome‐wide associations with flowering time in switchgrass using exome‐capture sequencing data. Issue 1 (22nd July 2016) - Grabowski, Paul P.; Evans, Joseph; Daum, Chris; Deshpande, Shweta; Barry, Kerrie W.; Kennedy, Megan; Ramstein, Guillaume; Kaeppler, Shawn M.; Buell, C. Robin; Jiang, Yiwei; Casler, Michael D.
Summary: Flowering time is a major determinant of biomass yield in switchgrass ( Panicum virgatum ), a perennial bioenergy crop, because later flowering allows for an extended period of vegetative growth and increased biomass production. A better understanding of the genetic regulation of flowering time in switchgrass will aid the development of switchgrass varieties with increased biomass yields, particularly at northern latitudes, where late‐flowering but southern‐adapted varieties have high winter mortality. We use genotypes derived from recently published exome‐capture sequencing, which mitigates challenges related to the large, highly repetitive and polyploid switchgrass genome, to perform genome‐wide association studies (GWAS) using flowering time data from a switchgrass association panel in an effort to characterize the genetic architecture and genes underlying flowering time regulation in switchgrass. We identify associations with flowering time at multiple loci, including in a homolog of FLOWERING LOCUS T and in a locus containing TIMELESS, a homolog of a key circadian regulator in animals. Our results suggest that flowering time variation in switchgrass is due to variation at many positions across the genome. The relationship of flowering time and geographic origin indicates likely roles for genes in the photoperiod and autonomous pathways in generating switchgrass flowering time variation.